Short-term Effects of Integrative Korean Medicine Treatment on Pain, Dysfunction, and Claudication in Patients with Degenerative Lumbar Spinal Stenosis: A Case Report - Sookwang An; Taewook Lee; Jihun Kim; Yoona Oh; Gi Young Yang; Eunseok Kim (Journal of Acupuncture Research)
Many Korean medicine doctors use Huatuo-HyupCheok (EX-B2) to treat degenerative lumbar spinal stenosis (LSS). However, research regarding its therapeutic effect and the direction of its application for LSS is limited. This study analyzed various parameters reported in clinical studies utilizing EX-B2 for treating LSS, including the treatment frequency, needling depth, and evaluation tools. Six databases were searched for articles published before March 17, 2024. Twenty-one studies were selected and analyzed. Various approaches were recommended for the application of EX-B2 in the treatment of LSS. The lumbar hyperextension test and deep tendon reflex test can be used for diagnosis. A personalized treatment approach can be applied based on traditional Chinese medicine syndrome differentiation. Treatment should be performed for at least 16 days using 0.30 × 40 mm filiform needles. Japan Orthopedic Association score, numerical rating scale, visual analog scale, and Roland Morris disability questionnaire can be utilized to assess the treatment effectiveness. Future systematic and continuous clinical studies are anticipated to develop more refined recommendations with a higher level of evidence.